143k views
3 votes
It always confuses me when they make me do the baby steps

It always confuses me when they make me do the baby steps-example-1

1 Answer

2 votes

A. Alright, we want to multiply one equation by a constant to make it cancel out with the second. Since the first equation has a "blank" y, let's multiply the first equation by 2.

3x-y=0 → 2(3x-y=0) = 6x - 2y = 0

5x+2y=22


The answer for this part would be: 6x - 2y = 0 and 5x + 2y = 22


B. So now we combine them:

6x - 2y = 0

+ + +

5x + 2y = 22

= = =

11x + 0 = 22 ← The answer


C. Now that we have the equation 11x = 22, we solve for x

11x = 22 ← Divide both sides by 11

x = 2 ← The answer


D. Now that we have x=2, we plug that back in to 5x+2y=22 and solve for y:

5(2)+2y = 22

10 + 2y = 22

2y = 12

y = 6


Therefore, the solution to this problem is x = 2 and y = 6


User Salem Ouerdani
by
5.5k points